Essays on household taxation and competition between heterogeneous firms - Oliveira, Érica Diniz (2014)
Essa tese é constituída por três artigos: 'Tax Filing Choices for the Household', 'Optimal Tax for the Household: Collective and Unitary Approaches' e 'Vertical Differentiation and Heterogeneous Firms'.